Enhancing Performance of SnO2-Based Dye-Sensitized Solar Cells Using ZnO Passivation Layer. (3rd October 2016) - Wanninayake, W. M. N. M. B.; Premaratne, K.; Rajapakse, R. M. G. R.
Abstract : Although liquid electrolyte based dye-sensitized solar cells (DSCs) have shown higher photovoltaic performance in their class, they still suffer from some practical limitations such as solvent evaporation, leakage, and sealing imperfections. These problems can be circumvented to a certain extent by replacing the liquid electrolytes with quasi-solid-state electrolytes. Even though SnO2 shows high election mobility when compared to the semiconductor material commonly used in DSCs, the cell performance of SnO2 -based DSCs is considerably low due to high electron recombination. This recombination effect can be reduced through the use of ultrathin coating layer of ZnO on SnO2 nanoparticles surface. ZnO-based DSCs also showed lower performance due to its amphoteric nature which help dissolve in slightly acidic dye solution. In this study, the effect of the composite SnO2 /ZnO system was investigated. SnO2 /ZnO composite DSCs showed 100% and 38% increase of efficiency compared to the pure SnO2 -based and ZnO-based devices, respectively, with the gel electrolyte consisting of LiI salt.